Bat species on Timor Island, Indonesia - FADLAN PRAMATANA; MHD MUHAJIR HASIBUAN; RIZKI KURNIA TOHIR; CHRISTO EDUARDUS TAE; FARIS FATHUROHMAN; IBNU MARYANTO; SIGIT WIANTORO; NANANG SUPRIATNA; I GUSTI BAGUS ADWITA ARSA; NIXON RAMMANG; ALOYSIUS MARAWALI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pramatana F, Hasibuan MM, Tohir RK, Tae CE, Fathurohman F, Maryanto I, Wiantoro S, Supriatna N, Arsa IGBA, Rammang N, Marawali A. 2025. Bat species on Timor Island, Indonesia. Biodiversitas 26: 564-571. Timor Island, East Nusa Tenggara Province, Indonesia, is one of the Lesser Sunda regions with unique biodiversity. Updating information as a database needs to be carried out to become the basis for conservation actions at the species and ecosystem levels, considering that bat species are very vulnerable to habitat destruction. This research aims to collect a checklist of bat species on Timor Island by selecting sampling locations based on the habitat's climatic conditions. The study was conducted in 10 research locations, including conservation, forest, village, and one disturbance area. Data was collected using mist nets, harp traps, and interviews with local communities. Suppose there is a record or a species that is doubtful in its identification, a specimen will be made and will then send samples to the Museum Zoologicum Bogoriense, Indonesia. Bat research in the Timor Island area was carried out in 1979 and recorded twenty-two species of bats. However, the locations in that research are spread across the Timor Leste region. This study on Timor Island, Indonesia, recorded twenty bat species, including a new record of Dobsonia viridis in the Lesser Sunda Island region. This species was previously documented only in Celebes and Moluccas.